Dietary Nitrate Supplementation Reduces Circulating Platelet-Derived Extracellular Vesicles in Coronary Artery Disease Patients on Clopidogrel Therapy: A Randomised, Double-Blind, Placebo-Controlled Study - Burnley-Hall, Nicholas; Abdul, Fairoz; Androshchuk, Vitaliy; Morris, Keith; Ossei-Gerning, Nick; Anderson, Richard; Rees, D. Aled; James, Philip E. (Thrombosis and Haemostasis, 2018)
Extracellular vesicles (EVs) are implicated in the pathogenesis of cardiovascular disease (CVD). Specifically, platelet-derived EVs are highly pro-coagulant, promoting thrombin generation and fibrin clot formation. Nitrate supplementation exerts beneficial effects in CVD, via an increase in nitric oxide (NO) bioavailability. Clopidogrel is capable of producing NO-donating compounds, such as S-nitrosothiols (RSNO) in the presence of nitrite and low pH. The aim of this study was to assess the effect of nitrate supplementation with versus without clopidogrel therapy on circulating EVs in coronary artery disease (CAD) patients. In this randomized, double-blind, placebo-controlled study, CAD patients with (n = 10) or without (n = 10) clopidogrel therapy received a dietary nitrate supplement (SiS nitrate gel) or identical placebo. NO metabolites and platelet activation were measured using ozone-based chemiluminescence and multiple electrode aggregometry. EV concentration and origin were determined using nanoparticle tracking analysis and time-resolved fluorescence. Following nitrate supplementation, plasma RSNO was elevated (4.7 ± 0.8 vs 0.2 ± 0.5 nM) and thrombin-receptor mediated platelet aggregation was reduced (−19.9 ± 6.0 vs 4.0 ± 6.4 U) only in the clopidogrel group compared with placebo. Circulating EVs were significantly reduced in this group (−1.183e11 ± 3.15e10 vs −9.93e9 ± 1.84e10 EVs/mL), specifically the proportion of CD41+ EVs (−2,120 ± 728 vs 235 ± 436 RFU [relative fluorescence unit]) compared with placebo. In vitro experiments demonstrated clopidogrel–SNO can reduce platelet-EV directly (6.209e10 ± 4.074e9 vs 3.94e11 ±  1.91e10 EVs/mL). In conclusion, nitrate supplementation reduces platelet-derived EVs in CAD patients on clopidogrel therapy, increasing patient responsiveness to clopidogrel. Nitrate supplementation may represent a novel approach to moderating the risk of thrombus formation in CAD patients.
Keywords: extracellular vesicles; clopidogrel; nitrate; nitrite; nitric oxide